Anion-Modulated Platinum for High-Performance Multifunctional Electrocatalysis toward HER, HOR, and ORR - Zonghua Pu; Ruilin Cheng; Jiahuan Zhao; Zhiyi Hu; Chaofan Li; Wenqiang Li; Pengyan Wang; Ibrahim Saana Amiinu; Zhe Wang; Min Wang; Ding Chen; Shichun Mu (iScience, 2020)
Summary: Efficient electrocatalyst toward hydrogen evolution/oxidation reactions (HER/HOR) and oxygen reduction reaction (ORR) is desirable for water splitting, fuel cells, etc. Herein, we report an advanced platinum phosphide (PtP2) material with only 3.5 wt % Pt loading embedded in phosphorus and nitrogen dual-doped carbon (PNC) layer (PtP2@PNC). The obtained catalyst exhibits robust HER, HOR, and ORR performance. For the HER, a much low overpotential of 8 mV is required to achieve the current density of 10 mA cm−2 compared with Pt/C (22 mV). For the HOR, its mass activity (MA) at an overpotential of 40 mV is 2.3-fold over that of the Pt/C catalyst. Interestingly, PtP2@PNC also shows exceptional ORR MA which is 2.6 times higher than that of Pt/C and has robust stability in alkaline solutions. Undoubtedly, this work reveals that PtP2@PNC can be employed as nanocatalysts with an impressive catalytic activity and stability for broad applications in electrocatalysis.